MRI of complex regional pain syndrome in the foot. Issue 129 (August 2020) - Agten, Christoph A.; Kobe, Adrian; Barnaure, Isabelle; Galley, Julien; Pfirrmann, Christian W.; Brunner, Florian
Highlights: MRI cannot distinguish between CRPS and non-CRPS patients. MRI's role in CRPS is to exclude alternative diagnoses. Bone marrow edema was absent in up to 50 % of CRPS patients. Abstract: Purpose: To evaluate the diagnostic potential of MRI in patients with suspected CRPS (complex regional pain syndrome). Method: A retrospective health-record search was conducted for patients with suspected CRPS (foot). Fifty patients with initially suspected CRPS were included (37 females (51 ± 13 years) and 13 males (44 ± 15 years)). All patients underwent MRI. Two radiologists assessed skin, bone, and soft tissue parameters on MRI. The final diagnosis was CRPS (Gold standard: Budapest criteria) or non-CRPS. MRI parameters were compared between CRPS patients and non-CRPS patients. Results: CRPS was diagnosed in 22/50(44 %) patients. Skin thickness (1.9 ± 0.5 mm vs. 1.7 ± 0.3 mm, p = 0.399), enhancement, and subcutaneous edema showed no differences between CRPS and non-CRPS patients. Bone marrow edema presence and pattern were not different between groups. Up to 50 % of CRPS patients showed no bone marrow edema. Subcortical enhancement and periosteal enhancement were not different between groups. For reader 1, muscle edema score was higher in the non-CRPS group compared to the CRPS group (0.1 ± 0.2 vs. 0.6 ± 1.0, p = 0.008), but not different for reader 2 (0.1 ± 0.5 vs. 0.2 ± 0.8, p = 0.819). Perfusion pattern was more extensive in non-CRPS patients for reader 1 (p = 0.048), but not for reader 2 (p = 0.157). Joint effusions showed no difference between groups. Conclusions: MRI cannot distinguish between CRPS and non-CRPS patients. The role of MR imaging in patients with suspected CRPS is to exclude alternative diagnoses that would better explain patients' symptoms.